(untitled) (Indonesian Journal of Civil Engineering Study, 2026)
This study examines the mechanical and durability properties of concrete incorporating a binary supplementary cementitious material (SCM) comprising ceramic waste powder (CWP) and activated zeolite (AZ) in a 1:1 ratio. Six concrete mixes with cement replacement levels of 0%, 10%, 15%, 20%, 25%, and 30% were assessed under exposure to 5% Na₂SO₄ and 3.5% NaCl. Durability testing involved wet-dry cycling for 28, 56, and 90 days. The results indicate that the mix with 20% CWP-AZ (M3) exhibited optimal performance, retaining over 92% of its strength, achieving the lowest sorptivity (0.221 mm/√s), and demonstrating a significant reduction in mass loss (2.1%) ANOVA (F = 14.72, p < 0.001) and regression modeling confirmed significant durability gains. The findings offer a sustainable solution for concrete used in offshore and oilfield infrastructures.